Pacific Islands - Fisheries sector engagement strategy - World Bank (World Bank, 2012)
The World Bank's 11 Pacific Island member countries are a diverse group in terms of economic and social conditions. Five are least developed countries, with annual per capita Gross Domestic Product (GDP) as low as US$ 700, while in some of the territories average incomes are comparable to those in wealthy industrialized countries. Population densities and growth rates, land areas and the level of urbanization all display similarly wide ranges. There is a great diversity of cultures and languages. What they have in common is that all are islands surrounded by the Pacific Ocean, with jurisdiction over areas that are many times (in some cases thousands of times) their land area. All derive significant economic and social benefits from their marine resources, with many coastal communities depending on them for their livelihoods. Several have large and important freshwater fisheries. All identify their living aquatic resources (for fisheries, aquaculture and non-extractive uses mainly related to tourism) as a major opportunity for economic growth and development. In some cases, they represent one of the only opportunities. Reviews of the importance of fish as a source of food for Pacific Island populations have found that annual per capita consumption of fishery products in all cases exceeds the global average of 16.5 kg. In several small island countries, where opportunities to produce other food are very limited, fish consumption is among the highest in the world. Fishing also plays an important cultural role for men and women in many of the region's coastal communities.